Board games como atividades experimentais no aprendizado de análise combinatória e raciocínio lógico - Santos, Evandro Rodrigues dos (2018)
Analyzing the context of education is the search for tools that allow a more meaningful and interesting learning for students. In this dissertation, we use board games as experimental activities, trying to understand how they contribute to the learning of combinatorial analysis and mathematical logical reasoning in High School. For this, we elaborated a mini course that contemplated a theoretical part with diagnostic test of knowledge and explanation of content, besides a practical part, that was our greater focus. We took as a methodology, Didactic Engineering that guided all the work, associated with the Didactic Sequences that shaped the application of each developed activity. Through it we observed a significant evolution in concentration, interaction, in the development of strategies, and in the logical reasoning that stimulated problem solving and developed a process of cooperative interaction that influenced learning. In this way, the activities contributed by stimulating in the students a more reasoned reasoning. They felt more confident and with the freedom to express their points of view and to defend it, which favored the attribution of a more comprehensive sense to what one studies in school.